Teachers and Students’ Assessment of Efficacy of Secondary School Social Studies Curriculum in Promoting Unity in Diversity in Nigeria - ADEGBITE, Dorcas Olayemi (Ilorin Journal of Education, 2023)
This study examined teachers and students’ assessment of efficacy of secondary school social studies curriculum in promoting unity in diversity in Nigeria. Descriptive survey research design was adopted for this study. The population of the study comprised all the public Upper Basic Social Studies teachers and students in Ibadan, Nigeria which is 326,917, while the target population consisted of all the public Upper Basic III Social Studies teachers and students in Ibadan, Oyo State, Nigeria which is estimated to be 24,583. Simple random sampling and purposive sampling approaches were used to select 430 respondents (400 Upper Basic III Social Studies students and 30 teachers) for the study. Researcher design instrument with reliability coefficients of 0.76 was used for data collection. The data collected were analysed using summated mean and independent t-test. The study revealed that the extent to which Social Studies Education promotes national unity among students in Nigeria was high; Social Studies Education classroom practices were effective in the attainment of national unity among students in Nigeria; and that Social Studies teachers and students were indifferent in their observation regarding the efficacy of secondary school social studies curriculum in promoting unity in diversity among students in Nigeria. It was concluded that Social Studies curriculum is efficacious in the promotion of unity in diversity in Nigeria. Based on this, it was recommended among others that Social Studies curriculum should be periodically reviewed to meet the current challenging situations capable of threatening the unity of the Nigeria.